EFEKTIVITAS SOAL OPEN- ENDED PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DI SEKOLAH MENENGAH PERTAMA - Susi Marisa (CV. Multi Kreasi Media, 2022)
Problem development is one way that can increase teacher knowledge about the achievement and level of students' thinking on learning materials. One of the consequences of the monotonous form of evaluation is the lack of freedom for students in solving problems so that students tend to be fixated on one solution and one correct answer. The purpose of this study was to develop open-ended questions on the material of a two-variable linear equation system and to determine student learning outcomes through an evaluation tool in the form of open-ended questions. The type of research used in this research is development research. This study develops questions and provides open-ended questions to determine student learning outcomes. After the questions are made, the questions are validated by experts. The validation of the questions was carried out by four validators. After validating, the next step is to revise according to the comments and suggestions of the validator. Based on the results of product trials, the questions are revised again if weaknesses are found. Furthermore, the questions that have been validated and tested for the product are tested for use in SMP Negeri 7 Jambi City. From the results of the analysis conducted on the use of open-ended questions, it was obtained that 67.74% of students' scores reached the good category. This means that it is an open-ended question that is made effective in its use.